Earth : the science of soil - Lerwill, Ben (Wonder world (Nosy Crow (Publisher)), 2026)
"From housing millions of worms, bugs, and microbes to providing enough nutrients to feed a planet worth of creatures, soil sustains life on Earth." Dig into soil difference, underground animal homes, microbes and other microorganisms that help things grow, fungi, and more.--From publisher description.